ПЕРВІСНИЙ ОРНАМЕНТ: ЗАСІБ ПРИКРАШАННЯ АБО СИМВОЛІКА ПРАДАВНЬОЇ МАГІЇ? (Педагогіка вищої та середньої школи, 2007)
The article is devoted to the origin, functions and symbolism of primitive images of decorative patterns. The special attention is spared to the constituents of decorative patterns of east slavs.